Application Of Educational Games in The Formation of Basic Competences in Primary Class Students - G.K. Seydanova; M. Yu. Kurbanova (Euro Asian Journal Publishing, 2024)
This article describes the methods of using educational games and the procedure for conducting games in the formation of basic competencies in elementary school students.
Keywords: competence; educational games; flexibility